Effect of degradative plasmid CAM-OCT on responses of Pseudomonas bacteria to UV light. - McBeth, D L (1989)
The effect of plasmid CAM-OCT on responses to UV irradiation was compared in Pseudomonas aeruginosa, in Pseudomonas putida, and in Pseudomonas putida mutants carrying mutations in UV response genes. CAM-OCT substantially increased both survival and mutagenesis in the two species. P. aeruginosa strains without CAM-OCT exhibited much higher UV sensitivity than did P. putida strains. UV-induced mutagenesis of plasmid-free P. putida was easily detected in three different assays (two reversion assays and one forward mutation assay), whereas UV mutagenesis of P. aeruginosa without CAM-OCT was seen only in the forward mutation assay. These results suggest major differences in DNA repair between the two species and highlight the presence of error-prone repair functions on CAM-OCT. A number of P. putida mutants carrying chromosomal mutations affecting either survival or mutagenesis after UV irradiation were isolated, and the effect of CAM-OCT on these mutants was determined. All mutations producing a UV-sensitive phenotype in P. putida were fully suppressed by the plasmid, whereas the plasmid had a more variable effect on mutagenesis mutations, suppressing some and producing no suppression of others. On the basis of the results reported here and results obtained by others with plasmids carrying UV response genes, it appears that CAM-OCT may differ either in regulation or in the number and functions of UV response genes encoded.